Microstructural characterization of Cr-doped (Bi, Sb)2Te3 thin films. Issue 26 (21st June 2017) - Tarakina, N. V.; Schreyeck, S.; Duchamp, M.; Karczewski, G.; Gould, C.; Brunner, K.; Dunin-Borkowski, R. E.; Molenkamp, L. W.
Abstract : We describe defects present in Cr-doped (Bi, Sb)2 Te3 thin films and suggest ways for controlling the structural quality of such films. Abstract : The presence of twins, both tilting and twisting of domains and resulting strain at domain boundaries in magnetically doped topological insulators can significantly modify their band topology and carrier density, and hence their electronic properties. In this paper, we report on a detailed microstructural characterization of Cr-doped (Bi, Se)2 Te3 layers grown by molecular beam epitaxy on Si(111). We provide detailed microscopical descriptions of defects present in the films (twins, mosaicity tilt, mosaicity twist), and suggest ways to control their structural quality.